Surveying dentistry students' perspectives on anatomy education: A questionnaire-based study: Survey of anatomy education among dentistry students - Kılıç Şafak, Nazire; Erdem, Hüseyin (Journal of Surgery and Medicine, 2024)
Background/Aim: Anatomy plays a crucial role in medical and dental education, equipping students with vital knowledge for comprehending the human body and its clinical implications. The COVID-19 pandemic led to a significant transition to online learning, raising questions about the efficacy of virtual anatomy education. Additionally, recent natural disasters like earthquakes have disrupted traditional learning settings, highlighting the need for alternative methods such as online instruction. This study sought to investigate dentistry students' opinions on anatomy education, specifically comparing the perspectives of students affected by earthquakes with those who were not, to determine any disparities in their attitudes towards online anatomy courses. Methods: A voluntary survey was conducted on 135 first-year students at Çukurova University Faculty of Dentistry during the 2023-2024 academic year. A 5-point Likert-type survey with 21 questions was used for data collection. Results were presented as percentages and analyzed. The Likert scale ranged from 1 = Strongly Disagree to 5 = Strongly Agree. Statistical analysis was performed using SPSS 20.0, including Kolmogorov-Smirnov and Shapiro-Wilk Tests for normal distribution assessment and the Mann-Whitney U-test for non-normally distributed scores comparison (P-value <0.05). Results: Students directly affected by earthquakes showed a significant difference in their perception of online education compared to unaffected students, particularly in the question "Theoretical anatomy course can be followed online" (P=0.036). Conclusion: This study provides insights for enhancing education planning and development based on student feedback.